2013
DOI: 10.5152/jtgga.2013.69320
|View full text |Cite
|
Sign up to set email alerts
|

Impact of earthquakes on sex ratio at birth: Eastern Marmara earthquakes

Abstract: Objective: Previous reports suggest that maternal exposure to acute stress related to earthquakes affects the sex ratio at birth. Our aim was to examine the change in sex ratio at birth after Eastern Marmara earthquake disasters. Material and Methods:This study was performed using the official birth statistics from January 1997 to December 2002 -before and after 17 August 1999, the date of the Golcuk Earthquake -supplied from the Turkey Statistics Institute. The secondary sex ratio was expressed as the male pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Summary of the main results. (A) Catalano et al, 2013; D'Alfonso et al, 2012; Doğer et al, 2013; Fukuda et al, 1998; Fukuda et al, 2018; Hamamatsu et al, 2014; Nandi et al, 2018; Saadat, 2008; Suzuki et al, 2016; Torche & Kleinhaus, 2012; Tourikis & Beratis, 2013. (B) Catalano et al, 2020; Grech & Borg, 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary of the main results. (A) Catalano et al, 2013; D'Alfonso et al, 2012; Doğer et al, 2013; Fukuda et al, 1998; Fukuda et al, 2018; Hamamatsu et al, 2014; Nandi et al, 2018; Saadat, 2008; Suzuki et al, 2016; Torche & Kleinhaus, 2012; Tourikis & Beratis, 2013. (B) Catalano et al, 2020; Grech & Borg, 2016.…”
Section: Resultsmentioning
confidence: 99%
“…There is a significant decline in SRB according to studies conducted in Bam (Saadat, 2008), Wenchuan (Tan et al, 2009), L'Aquila (D'Alfonso et al, 2012), Tarapaca (Torche & Kleinhaus, 2012), Gölcük (Doğer et al, 2013), East Japan (Suzuki et al, 2016), and Gujarat (Nandi et al, 2018). Two studies (D'Alfonso et al, 2012; Saadat, 2008) found a reduction in male births at 9 and 11 months after an earthquake, respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 9 Similarly, male genetic frailty may mean that male fetuses are less resilient, or conception of male fetuses is reduced during periods of maternal or population-based stress. 70 Changes to the secondary sex ratio have previously been demonstrated following population-wide stress events including earthquakes 7 , 8 , 71 73 and terrorist attacks. 70 …”
Section: Discussionmentioning
confidence: 97%
“…[ 5 ] The study done by Montenegro in Chile observed that there was an increased incidence of facial clefts in infants who were at the appropriate period during a major Earthquake in Chile, indicating the role of increased stress levels in the etiology of cleft lip and/or palate. [ 6 ] Surprisingly, Fracer F. C did not observe any association of emotional stress during pregnancy with cleft lip or palate. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…Some of them have supported the role of maternal stress as a contributory factor, while some have denied it. [ 2 3 4 5 6 7 ] We conducted this study with the objective of determining whether maternal stress could be a causal factor for the occurrence of nonsyndromic cleft lip and palate.…”
Section: Introductionmentioning
confidence: 99%